Using Cooperative Integrated Reading and Composition (CIRC) Technique to Teach Recount Text - Andi Tenrisanna Syam (English Education Journal, 2019)
The objective of the research was to find out whether the use of CIRC technique is effective to improve students’ reading skill at the eighth grade of MTsN Model Palopo. This research applied quasi-experimental. The population of this research was the eighth grade students of MTsN Model Palopo. The number of population was 270 students. The sample were class VIII A consisting of 30 students as experimental group and class VIII B consisting of 30 students as control group. The sampling technique in this research was purposive sampling. The instrument of the research was reading test. The writer gave pretest and posttest to the students. The result showed that the students` mean score of posttest in experimental group was 85.33 and pretest was 71.03. The mean score of posttest is higher than the mean score of pretest (85.33 71.03). While the mean score of posttest in control group was 72.46 and the mean score of pretest was 70.86. The mean score of posttest was higher than the mean score of pretest (72.44 70.86). The result of statistical analysis the experimental group for a level of significance 0.05 with degree of freedom (df) = 29; the probability value was smaller than α 0.00 0.5 and the result of statistical analysis for the control group showed that the probability value was bigger than α .074 0.05. As a result, there is a significant difference in reading achievement between the students who were taught by using CIRC technique and those who were taught by non-CIRC technique. Based on the result of this study, the writer concluded that the use of CIRC technique was effective to improve students’ reading skill.